An examination of communication apprehension among 11 to 12 year-old learners in Malaysian primary schools - Rajeindram, Priyadharishiny (2023)
Learners who experience communication apprehension (CA) have a tendency to avoid and withdraw from interactions, and subsequently have reduced opportunities for both language learning and mastery of language specific skills through verbal interactions in the classroom. There is a lack of understanding of CA phenomenon among young learners resulting in difficulty to identify and address CA at an early age. This research used a mixed method design through four studies to understand CA among young learners (11 – 12 years old) in Malaysian primary school classrooms.